The impact of tris(pentafluorophenyl)borane hole transport layer doping on interfacial charge extraction and recombination - Bidinakis, Konstantinos; Weber, Stefan A. L. (Beilstein Journal of Nanotechnology, 2025)
Selective charge transport layers have a strong influence on the overall efficiency and stability in perovskite solar cell devices. Specifically, the charge extraction and recombination occurring at the interfaces between the perovskite and these materials can be a limiting factor for performance. A lot of effort has been put into improving the conductivity of selective contacts, as well as the junction quality and energetic alignment with the absorber. On the hole extracting side, organic semiconductors have been extensively used due to their flexibility and favorable properties. Two of such compatible materials that have yielded high performing devices are the small molecule 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (spiro-OMeTAD) and the polymer poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA). In this work, we investigate the impact of hole transport layer doping on the performance and potential distribution in solar cells based on these materials. To do so on operating solar cells, we created samples with exposed cross-sections and examined their potential profile distributions with Kelvin probe force microscopy (KPFM), implementing our comprehensive measurement protocol. Using the Lewis acid tris(pentafluorophenyl)borane (BCF), we enhanced the hole extracting material/perovskite junction quality in spiro-OMeTAD and in PTAA based devices. Measurements under illumination show that the improvement is caused by a reduced recombination rate at the perovskite/hole transporter interface.
Keywords: cross-section; hole transport layer doping; Kelvin probe force microscopy; perovskite solar cells